Forecasting Euro area real GDP: optimal pooling of information - Oliver Hülsewig; Johannes Mayr; Timo Wollmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper proposes a new method of forecasting euro area quarterly real GDP that uses area-wide indicators, which are derived by optimally pooling the information contained in national indicator series. Following the ideas of predictive modeling, we construct the area-wide indicators by utilizing weights that minimize the variance of the out-of-sample forecast errors of the area-wide target variable. In an out-of-sample forecast experiment we find that our optimal pooling of information approach outperforms alternative forecasting methods in terms of forecast accuracy.
Keywords: C13; C51; C53; C82; E37; 330; Forecasting; aggregation; model averaging; real time experiment; Konjunkturprognose; Europäische Wirtschafts- und Währungsunion; Prognoseverfahren; Aggregation; EU-Staaten